The new liberalism : (Cambridge University Press, 2001)
Liberal community: an essay in retrieval ; T. H. Green on dividual rights and the common good ; T. H. Green's complex common good: between liberalism and communitarianism ; Private property, liberal subject, and the state ; Neutrality, perfecttionism, and the new liberal conception of the state ; Bosanquet's communitarian defense of economic individualism: a lesson in the complexities of political theory ; The new liberalism and the rejection of untilitarianism ; staunchy modern, non - bourgeois liberalism ; The new liberalism and citizenship :